Helicobacter pylori and the microbiome in gastric cancer development and treatment: A year in review - P. Vieira; M. Barbedo-Tavares; C. Figueiredo (Microbiota in Health and Disease)
Gastric cancer remains a highly common and deadly disease. In the microbial world, Helicobacter pylori infection is the major risk factor that initiates a cascade of inflammatory responses and genetic alterations that drive gastric cancer development. In the context of chronic inflammation mediated by H. pylori, some patients may develop intestinal metaplasia, a lesion that is associated with an increased risk of developing gastric cancer. However, there is increasing evidence that, in addition to H. pylori, the non-H. pylori microbiome also plays a role in gastric carcinogenesis. Furthermore, the microbiome may influence the gastric tumor microenvironment and modulate response to treatment, in particular, treatment with immune checkpoint inhibitors. This article highlights research related to these topics published between April 2023 and March 2024. The integration of findings on the complex interplay of H. pylori and the microbiome in cancer initiation and progression will be crucial for the development of more effective prevention and therapeutic strategies.